APPLICATION OF SOLID-STATE NANOPORE TECHNOLOGY TO THE TRANSLATIONAL ANALYSIS OF OXIDATIVE DAMAGE THROUGH QUANTIFICATION OF 8-OXO-7, 8 DIHYDROGUANINE IN GENOMIC DNA - Abu Jalboush, Sara (Wake Forest University, 2025)
The quantification of 8-oxo-7,8-dihydroguanine (8-oxoGua) in genomic DNA (gDNA) is crucial for understanding its role in disease development and progression, particularly in cancer. However, current analytical techniques display a wide range of limitations that could be overcome by solid-state (SS)-nanopores, offering robustness, high sensitivity and convenience to the quantification of 8-oxoGua. We developed a selective SS-nanopore assay leveraged to quantify 8-oxoGua when coupled with tagging its specific location in the DNA with biotin. In this dissertation, we aimed at validating the utility of this assay in 8-oxoGua quantification in gDNA models from various sources.Several key objectives were achieved in this work. In chapter II, we enhanced the performance of the SS-nanopore assay by incorporating a polyhistidine-tagged monovalent streptavidin (hMS) and optimizing measurement conditions. Modifying the buffer pH and salt concentration enabled significant improvements in the stability, sensitivity and selectivity of the assay evidenced by micro-RNA (miRNA) quantification in human plasma at low concentrations. The assay’s feasibility and convenience were also enhanced evidenced by the observed broadening of device diameters feasible for the measurement. In chapter III, we validated the SS-nanopore assay for quantifying 8-oxoGua in gDNA. We first achieved high efficiency and specificity in 8-oxoGua labeling reaching up to 97%. Additionally, we successfully quantified 8-oxoGua in gDNA exposed to Hydrogen Peroxide (H₂O₂), showing strong correlations with mass spectrometry, the golden standard. Finally, we applied the optimized SS-nanopore assay to study 8-oxoGua formation and repair in a matched model of head and neck squamous cell carcinoma (HNSCC) cell lines with varied radiosensitivity to establish its translational capability in chapter IV. Our approach was able to detect potential mechanistic differences between the radio-sensitive and resistant phenotypes. Through this work, we established the SS-nanopore assay developed by our lab as a promising tool able to accurately quantify 8-oxoGua in gDNA. This method addresses the limitations of traditional techniques, providing a reliable and convenient tool. Our findings also contributed to our understanding of 8-oxoGua's role in cancer radio-resistance and opened new avenues for its use as a biomarker in cancer research and treatment response assessment.
Keywords: 8-oxoguanine; Head and neck squamous cell carcinoma; Mass spectrometry; Quantification; Radiation; Solid-state nanopores